Antibiofilm activity of irrigating solutions associated with cetrimide. Confocal laser scanning microscopy - Guerreiro-Tanomaru, J. M. [UNESP]; Nascimento, C. A. [UNESP]; Faria-Junior, N. B. [UNESP]; Graeff, M. S. Z.; Watanabe, E.; Tanomaru-Filho, M. [UNESP] (Wiley-Blackwell, 2014)
AimTo evaluate the antibiofilm activity of sodium hypochlorite (NaOCl) and chlorhexidine (CHX) solutions associated with cetrimide (CTR), and QMiX using confocal laser scanning microscopy.MethodologyEnterococcus faecalis (ATCC- 29212) biofilms were induced on bovine dentine blocks for 14days. The dentine blocks containing biofilm were immersed for 1min in the following solutions: 2.5% NaOCl; 2.5% NaOCl+0.2% CTR; 2% CHX; 2% CHX+0.2% CTR; 0.2% CTR; QMiX. After contact with the solutions, the dentine blocks were stained with Live/Dead((R)) BacLight for analysis of the remaining biofilm using confocal laser scanning microscope. Images were evaluated using the BioImage_L software to determine the total biovolume (m(3)), the green biovolume (live cells) (m(3)) and the percentage of substrate coverage (%). The data were subjected to nonparametric statistical test using Kruskal-Wallis and Dunn's tests at 5% significance level.ResultsAfter exposure to irrigants, the total biovolume observed for CHX, CHX+CTR, CTR, QMiX was similar to distilled water (P>0.05). NaOCl and NaOCl+CTR had the lowest total and green biovolume. The CTR and QMiX had intermediate green biovolume, with greater antibacterial activity than CHX and CHX+CTR (P<0.05). The NaOCl and NaOCl+CTR solutions were associated with microorganism removal and substrate cleaning ability.ConclusionsNaOCl and NaOCl+CTR solutions were effective on microorganism viability and were able to eliminate biofilm. The addition of cetrimide did not influence antibacterial activity.
Keywords: biofilm; chlorhexidine; confocal laser scanning microscopy; Enterococcus faecalis; sodium hypochlorite